Pengaruh Penggunaan Media Animasi dan Pengetahuan Awal Siswa Terhadap Hasil Belajar Siswa pada Materi Sistem Pencernaan Makanan Manusia di Sekolah Menengah Pertama - Ridho, Muhammad; Hasruddin, Hasruddin; Djulia, Ely (Jurnal Pendidikan Biologi, 2017)
This study aims to determine the effect of learning media animation, torso, and the image and initial knowledge of students on student learning outcomes on the material digestion system of human food class XI in Private High School Hang Tuah Belawan. The type of research used is quasi experiment with research pretest-postest control group design. Samples were selected using cluster sampling techniques and divided into experimental and conventional classes. In class XI IPA1 applied animation media, class XI IPA2was applied torso media, and class XI IPA3 applied conventional media. Multiple-choice questions are used to measure learning outcomes, while critical thinking skills are essay-based. Data analysis technique using Covarian Analysis (Anacova) at significant level Î±= 0,05 and continued with Tukey test with SPSS 21.0 software. The results showed that: (1) There is influence of animation media to student learning outcomes (F= 4,266; P= 0.017). Students who were taught by animation media were significantly different from the students who were taught by the image media, but not significantly different from those taught by torso media; and (2) There is influence of students early knowledge to result of student learning (F= 3,662; P= 0,011). Students with high initial ability who were taught by animation media, torso and gambart did not differ significantly with students who had low initial ability that was taught by torso animation media and images. Students who have high initial ability that dibelajarkan with media animation, torso and images significantly higher than students who have low initial ability that dibelajarkan with animation media, torso and gambar.Hasil research shows that learning using animation media and early knowledge is better in giving influence to learning outcomes.